O-3 Population pharmacokinetics and dosing optimisation of ceftriaxone in burn infants and children. Issue 10 (20th September 2017) - Zhao,
Abstract : Background: Ceftriaxone, a broad spectrum cephalosporin, used as first-line empirical antimicrobial therapy in burn children. Burn injury had shown significant impact on pharmacokinetics of antimicrobials. As paediatric data are limited, our aim was to evaluate the population pharmacokinetics of ceftriaxone in burn infants and children and define the appropriate dose in order to optimise antimicrobial treatment. Methods: Blood samples were collected from paediatric patients treated with ceftriaxone and concentrations were quantified by HPLC-UV. Population pharmacokinetic analysis was performed using NONMEM software. Results: The data from 50 paediatric patients (age range: 0.6–4.8 years) were available for population pharmacoki-netic analysis. A one-compartment model with first-order elimination showed the best fit with the data. A covariate analysis identified that age and weight had significant im-pact on ceftriaxone pharmacokinetics. A dose regimen of 50 mg/kg/day every 12 hour for infants and 75 mg/kg/day every 12 hour for young children produces satisfactory target attainments, using the standard MIC of 0.5 mg/litre. Conclusion: The population pharmacokinetics of ceftri-axone was evaluated in burn infants and young children and an optimal dosing regimen was established based on simulation.